Cover Feature: Disappearing Polymorphs in Metal–Organic Framework Chemistry: Unexpected Stabilization of a Layered Polymorph over an Interpenetrated Three‐Dimensional Structure in Mercury Imidazolate (Chem. Eur. J. 8/2020). Issue 8 (21st January 2020) - Speight, Isaiah R.; Huskić, Igor; Arhangelskis, Mihails; Titi, Hatem M.; Stein, Robin S.; Hanusa, Timothy P.; Friščić, Tomislav
Abstract : The "disappearing polymorph" phenomenon in metal–organic frameworks has been demonstrated and presents intermolecular agostic interactions, validated by Bader analysis of electron density shown in the image, as structure‐directing elements in such materials. More information can be found in the Full Paper by T. P. Hanusa, T. Friščić, et al. on page 1811 .